Employment and foreign direct investment : the Montenegro experience - Gardašević, Ana (Array, 2018)
The purpose of this study is to examine and better understand the effects of foreign direct investments on employment in Montenegro over the period from 2005-2017. Time series data on a quarterly basis, obtained from Central Bank of Montenegro, Statistical Office of Montenegro - MONSTAT and Employment Office of Montenegro were used in this research. To perform time series stationary testing, Dickey-Fuller test (ADF) and Perron test were used, i.e. the unit root tests, while the examination of the effects of foreign direct investments on employment was performed using the regression analysis with the least square method. The results of the research, obtained by the evaluation of the simple linear econometric model show that if foreign direct investments increase by 1%, employment in Montenegro can be expected to increase by an average of 0.0058%. However, the regression analysis results clearly show that over the total observed period, the influence of foreign direct investments on employment does not have statistical significance. The obtained results are not surprising, considering the fact that the observed period is characterized by a modest share of the greenfield investment within the total structure of foreign direct investments in the Montenegrin economy.